THE VISION OF THE INDIGENOUS COMMUNITIES OF THE SIERRA P’URHÉPECHA AROUND PRIMORDIAL TITLES (Tzintzun, Revista de Estudios Históricos, 2024)
This article addresses the issue of the primary titles of the indigenous communitiesof the Sierra P’urhépecha, in the state of Michoacán. The P’urhépecha perspectiveregarding their own pictographic and alphabetic documents is particularlyexposed, with greater attention to the definitions of the documents from theP’urhépecha language. The concepts of k’uirakua are analyzed, the case of theLienzo de Comachuen, echeri míntakua, atánskatecha, eránhikua p’itákatecha,kuirútsikatecha, karánskata p’itákatecha, mienskuecha, uaripitarakuecha andkuapitarakurhikuecha, framed in the notion of tua anapu karákatecha, ancientwritings or old documents.
Keywords: primordial title; memory; territory; vision of the communities; tua anapu